An empirically derived model of inhibitors to information technology (IT) use in a Caribbean firm - Louis, Stephen (Cranfield University, 2007)
The research investigated the use of IT in Caribbean firms with particular emphasis on identifying inhibitors preventing firms from deriving the desired level of benefit from Information Technology (IT) in their efforts to improve competitiveness. It was conducted within the interpretive paradigm, and used a combination of data collection methods, namely interviews, participant observation and review of documentary evidence. The research was conducted in Caribbean-owned firms in St Lucia and Barbados, and was predicated on an argument that the business environment in the Caribbean was becoming more competitive, and that there was an expectation that IT would assist firms in the Caribbean to respond to the increased competition. An initial exploratory study based on interviews with 10 IT and business managers in 7 firms in St Lucia and Barbados supported the initial argument that the business environment was becoming more competitive. It also confirmed that managers believed that IT would assist their firms in becoming more competitive. However, the research showed that the firms were only deriving limited competitive benefits from their IT. An in-depth multi-case study was carried out using 3 business units within a single firm in St Lucia. The study investigated the specific inhibitors that were preventing the firms from obtaining greater benefit from IT. The results revealed that while inhibitors are usually conceptualized and reported in the research literature as distinct factors, when viewed from the perspective of the managers, they were in fact highly interrelated. The study contributes to a small but growing body of literature that is based on the argument that inhibitors are important factors that need to be investigated separately, rather than being conceptualized as merely the opposite of enablers. The study also demonstrates that the identification of inhibitors can be used as part of a diagnostic process for improving the benefits that firms derive from the IT investment.